The training of Olympic wrestling coaches: study of the sources of knowledge and essential training contents - Martins, P.; Rosado, A. (Revista de Artes Marciales Asiaticas, 2017)
The aim of this study was to analyze the representation of wrestling coaches regarding the sources of knowledge and the training contents to be adopted during the training process of young wrestlers` coaches. The study was based on Grossman`s (1990) model of professional knowledge for teaching and followed a qualitative, multiple case study methodology. Following a semi-structured script, six Olympic wrestling experts were interviewed in-depth, trying to identify the sources of knowledge that the coaches used for their training and what didactic-methodological contents they considered essential to play their role as coach. The analysis revealed that the coaches` sources of professional knowledge were diverse, including academic training and professional experience as the main sources of access to professional knowledge. The coaches also pointed out that their first sources of knowledge were their experiences as competitive athletes. Finally, this study concludes that expert coaches must acquire a profound knowledge of the competition environment, seeking to optimize their influence on athletes, which should extend not only to the sport practice of the youngster - as an athlete - but also at the level of the athlete as a person.